Contemporary management of lymph node metastases from an unknown primary to the neck: II. A review of therapeutic options1. Issue 2 (27th October 2011) - Strojan, Primož; Ferlito, Alfio; Langendijk, Johannes A.; Corry, June; Woolgar, Julia A.; Rinaldo, Alessandra; Silver, Carl E.; Paleri, Vinidh; Fagan, Johannes J.; Pellitteri, Phillip K.; Haigentz, Missak; Suárez, Carlos; et al.
Abstract Although uncommon, cancer of an unknown primary (CUP) metastatic to cervical lymph nodes poses a range of dilemmas relating to optimal treatment. The ideal resolution would be a properly designed prospective randomized trial, but it is unlikely that this will ever be conducted in this group of patients. Accordingly, knowledge gained from retrospective studies and experience from treating patients with known head and neck primary tumors form the basis of therapeutic strategies in CUP. This review provides a critical appraisal of various treatment approaches described in the literature. Emerging treatment options for CUP with metastases to cervical lymph nodes are discussed in view of recent innovations in the field of head and neck oncology and suitable therapeutic strategies for particular clinical scenarios are presented. For pN1 or cN1 disease without extracapsular extension (ECE), selective neck dissection or radiotherapy offer high rates of regional control. For more advanced neck disease, intensive combined treatment is required, either a combination of neck dissection and radiotherapy, or initial (chemo)radiotherapy followed by neck dissection if a complete response is not recorded on imaging. Each of these approaches seems to be equally effective. Use of extensive bilateral neck/mucosal irradiation must be weighed against toxicity, availability of close follow‐up with elective neck imaging and guided fine‐needle aspiration biopsy (FNAB) when appropriate, the human papillomavirus (HPV) status of the tumor, and particularly against the distribution pattern (oropharynx in the majority of cases) and the emergence rate of hidden primary lesions (<10% after comprehensive workup). The addition of systemic agents is expected to yield similar improvement in outcome as has been observed for known head and neck primary tumors. Head Neck, 2013